Perceived unappealing qualities of the opposite sex considered by single since birth adolescents in choosing a romantic partner - Razon, Maricel SJ (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT The study aimed to identify the perceived unappealing qualities in a prospective romantic partner of Single Since Birth (SSB) adolescents; to categorize these qualities into common themes between gender and across socio-economic status (SES), and to identify the factor/s that may affect/s the emergence of such qualities. One hundred randomly selected SSB adolescents answered the survey questionnaire, among them thirty were interviewed. Data gathered from the survey were categorized using thematic tables and frequency distribution tables while interview results were analyzed using content analysis. Twelve themes emerged from the list of unappealing qualities: personality traits, hygiene, physical attributes, intellectual capabilities, vices, outlook in life, religion, socio-economic status (SES), gender-related issues, domestic skills, educational background and age related issues. The SES, educational background and outlook in life of males were uniquely important for female respondents while age-related issues and domestic skills of females were valued as important by males. Adolescents belonging to Bracket A showed the need to ensure homogeneity in terms of the socio-economic background of their prospective romantic partner. Finally, SSB adolescents were found to be influenced by various factors in coming up with their mate selection standards such as (a) personal beliefs, values and goals (b)family values and experiences (c) past experiences with the opposite sex (d) satisfaction of personal needs (e) health concerns (f) religion (g) peers and (h) educational background.